078 Incidence rates and survival trends of cancer in 0–29-year-olds by ethnic group in Yorkshire, UK. (16th November 2010) - van Laar, M; McKinney, P A; Parslow, R C; Glaser, A; Kinsey, S E; Lewis, I J; Picton, S V; Richards, M; Shenton, G; Stark, D; Norman, P; Feltbower, R G
Abstract : Objective: Few studies have examined differences in the epidemiology of cancer between ethnic groups for children and young adults in the UK. We investigated incidence rates, associated trends and survival by ethnicity (south Asian vs all other ethnic groups) across childhood (0–14) and young adult (15–29) ages using a unique specialist cancer register. Methods: The data used for this study were extracted from the Yorkshire Specialist Register of Cancer in Children and Young People. Patients diagnosed from 1990 to 2005 in the former Yorkshire Regional Health Authority were included in the analysis. Ethnicity was assigned using name analysis programs and Hospital Episode Statistics data. Incidence rates (per 1 000 000 person-years) by ethnic group were derived using mid-year population estimates. Poisson regression was used to examine trends in incidence by ethnicity and diagnostic sub-group, adjusting for sex and age. An interaction term between year and ethnicity was added to the model and likelihood-ratio test used to determine whether incidence trends differed for south and non south Asians. Survival rates were assessed using Kaplan-Meier estimates and log-rank tests. Cox regression was used to assess the effect of ethnicity on survival, adjusting for age, sex, year and deprivation. Results: Overall cancer incidence was similar for south Asians (12.1; 95% CI 10.7 to to 13.5, n=275) and non-south Asians (12.6; 95% CI 12.2 to to 13.1, n=3259). For non-south Asians, incidence rates increased on average by 1.5% per year (95% CI 0.8 to to 2.3); the rate of increase for south Asians was significantly higher (7.0%; 95% CI 4.2 to to 9.9). Survival rates were significantly poorer for 15–29 vs 0–14 year olds (HR 1.25; 95% CI 1.09 to to 1.43). A significant increased risk of death was seen for south Asians compared to non-south Asians with leukaemia (HR 1.76; 95% CI 1.10 to to 2.81) and lymphoma (HR 3.11; 95% CI 1.61 to to 5.99). South Asians with other solid tumours had a significantly reduced risk of death (HR 0.43 95% CI 0.23 to to 0.81) compared to non-south Asians. Conclusion: If present trends continue, the higher rate of increase seen among the Asian population in Yorkshire will result in 3-times higher incidence than non-south Asians by 2020. Lower survival rates seen for south Asians with leukaemia and lymphoma and for 15–29 year olds warrant further detailed investigation.